Distribuição de freqüência e temporal de chuvas intensas. - Quadros, Luciana Espíndula de (2008)
This work aiming at contribute for the planning of activities that are influenced by the intensity of hasty water, in that the results condition technical or strategic decisions of order in activities as farming, civil construction and tourism. It was analizy historical series of maximum haste for different durations obtained of raingouge in the town of Cascavel-PR, planning an intense rain probability distribution model through the distribution generalized be adjusted Moments LH for estimate his parameters and the statistical test proposed by Wang (1998) for verification of the quality of the settlements developed in the environment Matlab. Beyond that, them referred series were adjusted through the distribution Gumbel for effect of comparison with the GEV. The results show that the distribution of the kind VEI of the GEV, that corresponds the distribution Gumbel, is not adequate for big periods of return therefore substime the values of the distribution kind VEII. As results are presented the estimates of the parameters of the GEV, the values of the rates for the time being LH, the period of each return duration of rain and the hydrographs of project.